Regulating Internet access and content in UK public libraries: Findings from the MAIPLE project. (March 2015) - Spacey, Rachel; Cooke, Louise; Creaser, Claire; Muir, Adrienne
This paper reports the results of an online survey concerning the management of Internet access in UK public libraries. All UK public library authorities were invited to complete the survey which had a response rate of 39%. The survey explored the ways in which acceptable use of the Internet in public libraries is managed through the use of mechanisms such as filtering software and authentication of identity. All 80 responding public library authorities used filtering software. Procedures for authenticating identity for static Internet access were uniform whereas wireless access was much less regulated.